DAYAH SANTRI IN ACEH: Early History and Recently Development - Ali Buto, Zulfikar; Hafifuddin, Hafifuddin (Journal of Contemporary Islam and Muslim Societies, 2020)
Abstract: This article examines the early history and recent developments of dayah santri in Aceh. This research is a combination of library research and field research. The approach used in this study is a historical approach. This study proposes that the modernization of the santri is divided into two phases. The first phase of pre-modernization, modernization of Acehnese santri only recognizes the world of students wearing a kupiah (cap), sarong, balee, reciting the Koran 10-25 years ago, returning to the village, establishing a small dayah, and so on. The second phase is the modernization phase, in this phase, the students experience modernization, in which students begin to openly follow formal education from Elementary School to Higher Education (S1-S3). Santri have started to participate and compete for strategic positions in the government of the DPRA Chairperson, Head of Service, Businessman, Head of the Religious Office, Chair of Local and National Parties, and students have expanded and continued their academic education to several European countries such as England, Spain, Germany, Turky to Latin America.Keywords: santri, education, dayah, Aceh, modernization